Kompetensi Guru PAI Menggunakan Media Powerpoint Dalam Mengimplementasikan Kurikulum Merdeka di SMAN 1 Pantai Cermin Kabupaten Solok - Shafiyah, Amalia; N, Nurhasnah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
A teacher is expected to have four different types of competencies: pedagogical, personal, professional, and social. One of the important skills that a teacher must have is pedagogical competence. A teacher's ability to use learning media is one aspect of his pedagogical competence. Another is its ability to help students learn. One way to ensure an interesting learning process is to use educational media. One tool that can help teachers is learning media. This can also make it easier for students to understand and remember the material being taught. In their learning, the class PowerPoint media. The research methodology used is qualitative research using observation, interview and documentation techniques. Based on research findings, Islamic education teachers' proficiency in using PowerPoint involves three stages: preparation, implementation, and follow-up. Meanwhile, the obstacle faced by Islamic Religious Education teachers in using Powerpoint media is the lack of support for WiFi and speakers to support teachers in using Powerpoint media. Apart from that, the obstacle for teachers in using Powerpoint media is that teachers still use the same type of design, writing and appearance for each learning topic.